Kinematics and dynamics analysis of a new-type friction stir welding robot and its simulation. (July 2019) - Luo, Haitao; Fu, Jia; Jiao, Lichuang; Liu, Guangming; Yu, Changshuai; Wu, Tingke
The mechanical configuration, structural composition, and five typical working conditions of a newly developed friction stir welding robot are introduced. The kinematics model of the friction stir welding robot is established and the forward kinematics equations, inverse kinematics equations, and the Jacobian matrix are solved. In addition, the dynamics model of the friction stir welding robot is also built by using the Lagrange method. The centroid position coordinate and inertia matrix of each part are obtained. Finally, the dynamic equation of friction stir welding robot is determined. According to the kinematics and dynamics model of robots, simulation analysis for friction stir welding robot based on virtual prototyping technology was carried out. The trajectory equation of the weld joint under the condition of melon petal welding is established, the spline trajectory is fitted by many discrete points measured by the contact probe, and the trajectory planning of each joint and the changing laws of motion parameters under the friction stir welding robot melon petal welding condition are obtained. The movement laws and the loading conditions of each joint can be better controlled by designers, and provide solid theoretical support for the static and dynamic characteristics analysis and structural optimization of the friction stir welding robot.